PEMBINAAN NILAI SPIRITUAL DAN SOSIAL ISLAMI PESERTA DIDIK DI LINGKUNGAN PENDIDIKAN MINORITAS MUSLIM - Yusron Hasbi (Lembaga Pengembangan Kinerja Dosen, 2022)
The conditions of the educational environment have an impact on the spiritual and social values of students. The school environment is often part of what shapes the personality of students, so muslim students who study in educational institutions that are minority muslims know a lot about cultures that are far different from islamic teachings. Therefore, this study aims to reveal how Islamic spiritual and social coaching of students in the educational environment of Muslim minorities. The research was conducted by SMA Negeri 2 Sipora, the approach used was qualitative. Data were collected by observation techniques, interviews and documentation studies. Data analysis uses the techniques Huberman offers. The result of the study was that the spiritual value development carried out at SMA Negeri 2 Sipora was in the form of establishing regular dhuha and zuhur prayer activities, tadarus al-Qur'an, a special cultum of Muslim students, instilling an attitude of respect for every elder. Meanwhile, the development of Islamic social values to Muslim students in the Muslim minority education environment is to emphasize honest behavior, discipline, responsibility, courtesy, tolerance, self-confidence, mutual cooperation. These values found are realized at SMA Negeri 2 Sipora due to the application of learning methods that are in line with environmental conditions and student conditions.